Evidence for susceptibility determinant(s) to psoriasis vulgaris in or near PTPN22 in German patients. Issue 6 (9th December 2005) - Hüffmeier, U; Steffens, M; Burkhardt, H; Lascorz, J; Schürmeier-Horst, F; Ständer, M; Kelsch, R; Baumann, C; Küster, W; Mössner, R; Reich, K; Wienker, T F; et al.
Abstract : Introduction: Variant R620W of protein tyrosine phosphatase non-receptor type 22 ( PTPN22 ) has consistently been reported as a susceptibility factor for several autoimmune diseases. We investigated its role in susceptibility to psoriasis, the relevance of possibly other disease-causing variants, and interdependency of the major risk factor for psoriasis at PSORS1. Methods: R620W was tested in a case-control study initially with 375 German patients and then with an enlarged sample of an additional 418 patients. Analyses were extended to linkage disequilibrium (LD) based haplotypes. Potential interaction between risk haplotypes of PTPN22 and the PSORS1 associated risk allele was tested by regression analysis. PTPN22 coding sequence was determined in 20 patients carrying the risk haplotype. Association and regression analysis were also performed in the extended case-control study. Results: R620W was not associated in either case-control study, while significant association (corrected for multiple testing) with one haplotype (C-4) of the LD block encompassing PTPN22 as well with another haplotype (B-3) within an adjacent telomeric LD block was detected. No evidence for interaction between risk haplotype C-4 and the PSORS1 associated risk allele was found. Sequencing excluded other coding variants within PTPN22 as a basis for association findings. Analysis of the extended study group confirmed association for haplotypes B-3 and C-4 and independence of risk haplotypes C-4 and PSORS1. Discussion: We exclude a major role of *620W in German psoriasis patients but suggest that other susceptibility determinant(s) within non-coding regions of PTPN22 or its proximity might exist acting independently of the major PSORS1 risk factor.